Tales of the unexpected. Incongruity-resolution in humor comprehension, scientific discovery and thought experimentation - De Mey, Tim (Logic and Logical Philosophy, 2005)
Some scholars suspect that thought experiments have something in common with jokes. Moreover, Thomas Kuhn has suggested that what happens to someone who thinks through a thought experiment “is very similar to what happens to a man, like Lavoisier, who must assimilate the result of a new unexpected experimental discovery” (1964: 321). In this paper, I pinpoint the presumed commonalities. I identify, more specifically, what cognitive linguists call “incongruity-resolution” as the problem-solving process not only involved in humor comprehension, but in scientific discovery and thought experimentation as well.